Biomechanical Contribution of Tension-Reducing Rotator Cuff Sutures in 3-Part Proximal Humerus Fractures. Issue 8 (August 2016) - Arvesen, John E.; Gill, Stephen W.; Sinatra, Philip M.; Eng, Michael; Bledsoe, Gary; Kaar, Scott G.
Abstract : Objectives: Using a cadaveric 3-part fracture model and cyclic loading protocol, our study objectives were to quantify the stabilizing effect of tension-reducing rotator cuff sutures in terms of fracture displacement across the surgical neck and greater tuberosity compared with a control group in which no sutures were used. Methods: Six matched pairs of fresh frozen specimens underwent a standardized, 3-part, proximal humerus fracture and were split into 2 groups. The control group had the fracture fixed with a plate and screw construct only while the experimental group had additional suture fixation through the plate to each rotator cuff tendon. Active abduction through the rotator cuff was simulated for 100, 200, 300, and 400 cycles and to failure at 1000 N. A Mann–Whitney U test compared cyclic displacement of the greater tuberosity and surgical neck fracture gaps and load to failure between the 2 groups. Results: There was no significant difference ( P > 0.05) in fracture gap between fixation methods at the surgical neck at 100 ( P = 0.13), 200 ( P = 0.07), 300 ( P = 0.49), and 400 ( P = 0.07) cycles. There was no significant difference ( P > 0.05) between fixation methods in the fracture gap at the greater tuberosity at 100 ( P = 0.39), 200 ( P = 1.00), 300 ( P = 0.31), and 400 ( P = 0.59) cycles. There was no significant difference ( P > 0.5) at 1000 N at the surgical neck ( P = 0.70) or the greater tuberosity ( P = 0.39). Conclusions: Tension-relieving rotator cuff sutures do not add stability to the repair of 3-part proximal humerus fractures. Varus collapse and greater tuberosity displacement are common complications associated with 3-part fractures. No mechanical data exist to demonstrate benefit of adding suture to a plate and screw construct for limiting fracture displacement.